2019
DOI: 10.21873/anticanres.13827
|View full text |Cite
|
Sign up to set email alerts
|

The Value of CA19-9 After Irreversible Electroporation for Pancreatic Cancer

Abstract: Background/Aim: Carbohydrate antigen 19-9 (CA19-9) is a tumor marker for pancreatic cancer. Irreversible electroporation (IRE) is an experimental treatment modality for pancreatic cancer. The aim of this study was to evaluate whether percutaneous IRE lowers the CA19-9 level in pancreatic cancer and whether this correlates with improved overall survival. Patients and Methods: Seventy-one patients with locally advanced pancreatic cancer or local recurrence after resection were treated. Patients with missing data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…The incomplete ablation was more common in tumors with large tumor sizes, which might contribute to the inferior survival of LAPC patients after IRE treatment. Similar with previous study ( 18 ), our study also indicated that the changes of CA19-9 levels were an important reflection of tumor response of IRE. High levels of CA19-9 predicted poor survival in LAPC patients after IRE treatment.…”
Section: Discussionsupporting
confidence: 91%
“…The incomplete ablation was more common in tumors with large tumor sizes, which might contribute to the inferior survival of LAPC patients after IRE treatment. Similar with previous study ( 18 ), our study also indicated that the changes of CA19-9 levels were an important reflection of tumor response of IRE. High levels of CA19-9 predicted poor survival in LAPC patients after IRE treatment.…”
Section: Discussionsupporting
confidence: 91%